Ediacaran to Lower Ordovician age for rocks ascribed to the Schist–Graywacke Complex (Iberian Massif, Spain): Evidence from detrital zircon SHRIMP U–Pb geochronology - Talavera, Cristina; Montero, P.; Martínez Poyatos, D.; Williams, I. (Elsevier Science BV, 2012)
New SHRIMP U–Pb ages of detrital zircon obtained from eight samples of Neoproterozoic to Lower Paleozoic graywackes, schists, microconglomerates and shales provide the maximum depositional age and a new zircon age pattern for the Schist–Graywacke Complex (SGC) from the Iberian Massif (SW Europe). The ages of the youngest zircon grains found in four samples provide a maximum depositional age of latest Ediacaran–Lower Cambrian for the complex. Lower-Middle Cambrian fossiliferous formations on top of the lithologies correctly attributed to the SGC constrain its minimum depositional age. Unexpectedly, two samples attributed to the SGC yielded Cambro-Ordovician zircon populations. These must belong to younger Lower Ordovician sedimentary successions that, up to now, have not been differentiated from those of the SGC. The new age patterns are mainly composed of Neoproterozoic (73%) and Paleoproterozoic (15%) ages, with minor Neoarchean (7%), Mesoarchean (2%), Mesoproterozoic (3%) and Cambrian (1%) ages for the latest Ediacaran–Lower Cambrian successions, and Neoproterozoic (46%) and Cambro-Ordovician (46%) ages, with minor Neoarchean (1%), Mesoarchean (0.5%), Paleoproterozoic (6%), Mesoproterozoic (0.5%) and Carboniferous (1%) ages for the Lower Ordovician successions. The presence of Mesoproterozoic zircon points to the Saharan Metacraton as a contributing source for these sediments. Cadomian granitoids could have been a local Neoproterozoic source. The Cambro-Ordovician zircons may also indicate that Cambro-Ordovician magmatism contributed as a source. Cambro-Ordovician volcanism, the most probable source of the Cambro-Ordovician zircons, would have been coeval with the deposition of the Lower Ordovician successions.